PENERAPAN SMART JOYFUL JOURNALING FOR KIDS (SaJoJoKids) UNTUK MENINGKATKAN PEMBELAJARAN INOVATIF DAN RELIGIOUS HABITS SDN 4 BAWU - Sabilla, Alzena Dona; Muslimin, Khoirul; Wijanarko, KuKuh Dwi; Hamidaturrohmah, Hamidaturrohmah; Andriyani, Santi; Azizah, Noor (Jurnal Abdi Insani, 2025)
The low level of interest in learning and the lack of religious values at SDN 4 Bawu are major concerns in efforts to improve the quality of basic education. The lack of innovative and enjoyable learning methods and the suboptimal integration of religious character values in teaching and learning activities are the main factors influencing this situation. The objective of this community service activity is to improve the competence of teachers and students in applying innovative technology-based learning through Smart Joyful Journaling for Kids (SaJoJoKids) as a medium for literacy learning and religious habits. The community service method uses a service learning approach that includes the stages of socialization, training, mentoring, and reflective evaluation. Needs analysis was conducted through observation and interviews with teachers and students. The targets of this activity were classroom principals, teachers, educational staff of SDN 4 Bawu Jepara. The results showed that this activity contributed to an 89% increase in teachers’ knowledge in applying innovative technology-based learning. This program also had a positive impact on increasing students’ creativity in expressing religious values through digital daily journals, with an achievement rate of 84%. In addition, this activity became a support system that motivated teachers and students to continue developing fun and meaningful learning, with an achievement rate of 87%. Thus, this community service activity contributes significantly to improving the competence, skills, and religious character of school members directly